2009 IEEE Pulsed Power Conference 2009
DOI: 10.1109/ppc.2009.5386172
|View full text |Cite
|
Sign up to set email alerts
|

Fruit body formation of lentinula edodes by pulse electric field stimulations

Abstract: Pulsed high voltages were applied to logs for mushroom culturing to clarify an effect of the pulse voltage stimulation on fruit body formation of basidiomycetes i.e. mushroom. Inductive energy storage system was combined with Marx type pulsed power generator for construction of a pulsed power generator with compact size and high output voltage. The output voltage of 50 ns pulse width was applied to natural logs for culturing Lentinula edodes, Pholiota nameko and Naematoloma sublateritium as an electrical stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 10 publications
(10 reference statements)
0
10
0
Order By: Relevance
“…The pulsed power generator was constructed based on an IES system and was used to generate pulsed high voltages as electrical stimulation for mushrooms. The IES pulsed power generator basically consisted of primary energy storage capacitors, closing switches, a secondary energy storage inductor, and an opening switch [ 7 , 11 , 12 ]. The four primary energy storage 0.22 µF capacitors were connected in parallel and were charged up using a high-voltage dc power supply (50 kV maximum voltage).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The pulsed power generator was constructed based on an IES system and was used to generate pulsed high voltages as electrical stimulation for mushrooms. The IES pulsed power generator basically consisted of primary energy storage capacitors, closing switches, a secondary energy storage inductor, and an opening switch [ 7 , 11 , 12 ]. The four primary energy storage 0.22 µF capacitors were connected in parallel and were charged up using a high-voltage dc power supply (50 kV maximum voltage).…”
Section: Methodsmentioning
confidence: 99%
“…The application of a pulsed high voltage to improve the yield in edible mushroom cultivation has also been attempted by some research groups. The fruiting capacity of shiitake mushroom ( Lentinula edodes ; L. edodes ) was remarkably promoted by applying a pulsed high voltage to log wood [ 5 , 6 , 7 ]. This effect was also recognized in L. edodes fruiting on a mature sawdust-based substrate [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…found that pulsed electricity applied to the growing area increases mushroom yield. [ 63 ] The electricity may work by increasing the bioavailability of nutrients. In fact, another research group explored the effect of lightning on metal mobilization and its increased bioavailability after a strike; [ 64 ] and another describes the mobilization of phosphorus for ecosystem use after a strike.…”
Section: Results and Analysismentioning
confidence: 99%
“…The application of a pulsed high voltage to improve the yield in edible mushroom cultivation has also been attempted by some research groups. The fruiting capacity of shiitake mushroom ( L. edodes; L. edodes ) was remarkably promoted by applying a pulsed high voltage to log wood [1,2,3]. This effect was also recognized in L. edodes fruiting on a mature sawdust-based substrate [4,5].…”
Section: Introductionmentioning
confidence: 99%